Dry Fuel Jet Half-Angle Measurements and Correlation for an Entrained Flow Gasifier - Francis Kus; Robin Hughes; Arturo Macchi; Poupak Mehrani; Marc Duchesne (Energies, 2018)
Reduced order models (ROMs) are increasingly applied to entrained flow gasification development due to reduced computational requirements relative to computational fluid dynamics (CFD) models. However, they require greater a posteriori knowledge of the reactor physics. A significant parameter influencing ROM outputs is the jet half-angle of the solid fuel and oxidant mixture in the gasifier. Thus, it is important to understand the geometry of the jet in the gasifier, and how it is dependent on operating parameters, such as solid and carrier gas flow rates. In this work, an existing model for jet half-angles, which considers the ratio of surrounding gas density to jet core density, is extended to a dry solids jet with impinging gas. The model is fitted to experimental jet half-angles. The jet half-angle of a non-reactive flow was measured using laser-sheet imaging for solid fluxes in the range of 460–880 kg/m2·s and carrier gas fluxes in the range of 43–90 kg/m2·s at the transport line outlet. Jet half-angles ranged from 5.6° to 11.3°, increasing with lower solid/gas loading ratios. CFD simulations of two reactive conditions, with solid and gas fluxes similar to experiments, were used to test the applicability of the proposed jet half-angle model.